Clinical Outcomes After Dental Surgery with Two Antiseptic Protocols - Silvia D’Agostino (Dentistry Journal)
Background: Little has been written in the literature about the clinical comparison between the single use of chlorhexidine (CHX) and its combination with cetylpyridinium chloride (CPC). The purpose of this study is to compare the clinical effectiveness of two at-home antiseptic regimens. Methods: Healthy subjects scheduled for dental surgery were enrolled. After the surgery, patients were randomly allocated to the first group (group A), which received a manual ultrasoft toothbrush (Mentadent Professional®), an antiseptic toothpaste with 0.12% CHX and Vitamin B3 (Mentadent Professional Azione Intensiva Gengive®), and an antiseptic mouthwash with 0.12% CHX and 0.07% CPC. The second group (group B) solely received an antiseptic mouthwash with 0.2% CHX in conjunction with an anti-discoloration system (Curasept ADS/DNA®) and were encouraged to use their usual toothbrush and toothpaste. Patients were instructed to use the products twice a day and to rinse for 30 s. On day 7, patients were examined for the early healing score (EHS), visual plaque index (VPI) of the sutures, numerical rating scale (NRS), and mouthwash taste. Results: Group A showed a statistically significant level of EHS and taste satisfaction. VPI and NRS were different but not significant among the studied groups. Conclusions: The regimen based on CHX used in conjunction with vitamin B3 in the toothpaste and CPC in the mouthwash resulted in superior clinical outcomes and satisfaction compared to CHX alone.